ANALISIS URGENSI PENGEMBANGAN KOMIK DIGITAL DENGAN MENGINTEGRASIKAN NILAI-NILAI KEISLAMAN - Felzia Raneza; Hening Widowati (Universitas Muhammadiyah Metro, 2020)
Abstract: In the era of modern industrial technology 4.0, educators are required to be able to develop skills in making learning media that will be used with the help of technology. Comics are popular among teenagers where high school students are included. One type of comics, digital comics, has recently become a global trend, which is useful for use as an effective learning medium. To take advantage of this great opportunity, this study aims to analyze the importance of developing digital comics.The making of this digital comic uses the 4D model which is a development model that consists of 4 stages.